Evaluation of Progress of an ACGME-International Accredited Residency Program in Qatar - Al-Mohammed, Ahmed (Qatar Med J, 2020)
Background: The American College of Physicians’ (ACP) Internal Medicine In-Training Examination (IM-ITE) is designed to evaluate the cognitive knowledge of residents to aid them and program directors in evaluating the training experience. Objective: To determine the impact of the curriculum reform accompanied by the Accreditation Council for Graduate Medical Education (ACGME)-I alignment and accreditation on the internal medicine residency program (IMRP) using residents’ performance in the ACP's ITE from 2008 to 2016, and where the IMRP stands in comparison to all ACGME and ACGME-I accredited programs. Methods: This is a descriptive study conducted at a hospital-based IMRP in Doha, Qatar from 2008 to 2016. The study population is 1052 residents at all levels of training in IMRP. The ACP-generated ITE results of all the United States and ACGME-I accredited programs were compared with IM-ITE results in Qatar. These results were expressed in the total program average and the ranking percentile. Results: There is a progressive improvement in resident performance in Qatar as shown by the rise in total average program score from 52% in 2008 to 72% in 2016 and the sharp rise in percentile rank from 3rd percentile in 2008 to 93rd percentile in 2016 with a dramatic increase during the period 2013 to 2014 (from 32nd percentile to 73rd percentile), which represents the period of ACGME-I accreditation. None of the factors (ethnicity, USMLE or year of residency) were statistically significant with a p value >0.05 and standard coefficient ( − 0.017–0.495). There was negligible correlation between the USMLE test scores with the residents’ ITE scores with a p value = 0.023 and a Pearson correlation r = 0.097. Conclusion: The initial ACGME-I alignment followed by the accreditation, together with whole curriculum redesign to a structured, competency-based program starting from 2008, has led to an improvement in the ITE scores in the IMRP. This was further evidenced by the lack of change in the residency entry selection criteria.